2021
DOI: 10.3389/fcell.2021.624755
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Strain and Electrical Co-stimulation Improve Neural Differentiation of Marrow-Derived Mesenchymal Stem Cells

Abstract: The current study investigated the combinatorial effect of cyclic strain and electrical stimulation on neural differentiation potential of rat bone marrow-derived mesenchymal stem cells (BMSCs) under epidermal growth factor (EGF) and fibroblast growth factor 2 (FGF2) inductions in vitro. We developed a prototype device which can provide cyclic strain and electrical signal synchronously. Using this system, we demonstrated that cyclic strain and electrical co-stimulation promote the differentiation of BMCSs into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Various medical conditions result from abnormal skeletal muscle function [ 113 ]; these conditions include myopathies, paralysis, myasthenia gravis, urinary and/or intestinal incontinence, ataxia, weakness, tremors, and other disorders [ 114 ]. Nerve diseases can cause neuropathy and skeletal muscle dysfunction.…”
Section: Manual Therapy–tecar–hilt Therapy: Methods Of Use In the Tre...mentioning
confidence: 99%
“…Various medical conditions result from abnormal skeletal muscle function [ 113 ]; these conditions include myopathies, paralysis, myasthenia gravis, urinary and/or intestinal incontinence, ataxia, weakness, tremors, and other disorders [ 114 ]. Nerve diseases can cause neuropathy and skeletal muscle dysfunction.…”
Section: Manual Therapy–tecar–hilt Therapy: Methods Of Use In the Tre...mentioning
confidence: 99%
“…Actually, the possible mechanisms underlying the acquisition of neural fate regulated by electricity are focused on Ca 2+ spike and the subsequent activation of signaling pathways of adenylyl cyclase, which can elevate another second messenger, cyclic AMP (cAMP), initiating a cAMP signaling cascade to direct neuronal differentiation, axonal guidance, and neurite outgrowth. Notably, it is demonstrated that electrical stimulation and surface tension enriches local adhesion and ECM–receptor interaction signaling pathways, leads to increases of calcium and cAMP, and then activates MAPK and AKT pathways to promote differentiation of MSCs to neurons . This results above provide a systematic understanding of how biomechanical manipulation affects cell behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, ES generated by enzymatic biofuel cells was found to be able to change the cell morphology and gene expression of adipose mesenchymal SC (ASC) [155]. The combination of PC of 0.1 V/cm with a pulse duration of 0.04 ms at 10 Hz for 30 min daily up to 21 days in a 3D nanofibrillar cellulose hydrogel resulted in increased osteogenic potential in ASC [156]. A biphasic PC of 1 V/cm at 0.5 Hz in combination with cyclic strain was found to well differentiate the rat BMSC differentiation into neural cells [157].…”
Section: Stem Cell (Sc) Therapymentioning
confidence: 99%